Analysis of Thematic Appesception Test (TAT) to Identify Student Self-Endurance - Sudarsana, Gede Nugraha; Suarni, Ni Ketut; Ramli, M. (Department of Guidance and Counseling, FIP, Undiksha, 2022)
This study aims to describe students' self-endurance through Thematic Apperception Test (TAT) analysis. This research is descriptive. The sample in this study was high school/vocational students in Singaraja City, and data reduction was carried out using random sampling. Obtained a sample of 120 students from 3 schools. Data was collected using the Thematic Apperception Test. Data analysis categorizes the total score obtained by respondents based on TAT answers. Based on the results of the study, the average self-endurance indicators were obtained as follows: controlling the problem by 80%; finding the root of the problem by 85%; limiting the scope of the problem by 73%; survive and endure the problem by 82%. So it can be concluded that the TAT analysis can be used to identify students' self-endurance. The results of this study can be initial findings as an assessment method for educational institutions and related agencies in developing student character.